Prevention of genital prolapse recurrence in elderly women after surgery - Р. А. Сафонов; В. В. Лазуренко; О. Л. Черняк; О. А. Лященко; О. Б. Овчаренко (Publishing House TRILIST, 2020)
Genital prolapse (GP) is one of the leading gynecological diseases and is diagnosed in 30-50% of women, especially the elder ones. Its related disorders lead to social, psychological and clinical disorders in the form of social isolation, depression, sexual dysfunction, etc. Purpose of the study was to optimize the prevention of GP recurrence in elderly women after surgery. Materials and methods. 56 women aged from 60 to 82 with GP of III-IV degree of severity were examined and divided into 2 groups depending on the treatment method and prevention. 26 women in the first group were prescribed vaginal suppositories Revitaxа for 30 days after surgical treatment to increase the GP recurrence prevention. 30 women in the second group underwent traditional surgical treatment of GP without additional local therapy. Surgical treatment of women with GP included transvaginal extirpation of uterus without appendages, anterior colporrhaphy, colpoperineoraphy with levatoroplasty, sacrospinal colpopexy in 39 (69.6%) patients and anterior colporrhaphy, colpoperineoraphy with levatoperoplasty in 17 patients. Operation was supplemented by laparoscopic intervention due to the need to ovary remove in 2 women. Results. The proposed method of GP recurrence prevention in elderly women (unilateral sacrospinal fixation of the vaginal dome during surgical treatment of GP III-IV degrees which was followed by using vaginal suppositories Revitaxа for 30 days) allowed obtaining a 100% result in contrast to 90% in women with surgical treatment of GP without Revitaxа. Conclusion. The unilateral sacrospinal fixation of the vaginal dome during surgical treatment of GP III-IV degrees and using vaginal suppositories Revitaxа for 30 days after surgery is recommended to prevent the recurrence of GP in elderly women